BUDAYA FLEXING DI ERA MEDIA SOSIAL DALAM PERSPEKTIF HADIS - Melisa Haryati; Muhammad Alif (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
The culture of flexing on social media is commonly known as showing off wealth or achievements, which has an impact on society and ethics. This study aims to discuss the culture of flexing from the perspective of hadith. This study uses a qualitative approach by applying a thematic method. The formal research objects are the concept of riya' as minor shirk, the principle of intention in deeds, and the prohibition of takabbur, which have been formulated in accordance with the themes of the hadith. The research material objects are the various motives and forms of flexing behavior that occur in the current era of social media. The results of this study indicate that the themes of the hadith can be formulated in a theoretical framework to address the phenomenon of flexing on social media. The discussion of this research explains that, in the view of the hadith, the motive for flexing is often to obtain validation and praise from other people. The various forms of flexing range from showing off wealth, lifestyle, and other achievements. The impact of this behavior in the hadith is that the deeds become futile and become an obstacle to entering heaven because of arrogance. This study formulates solutions in the form of alternative digital ethics, including the virtue of doing good deeds in secret, humility, and maintaining sincerity. The conclusion of this study emphasizes that the cultural phenomenon of flexing can become a positive ethic if it prioritizes right intentions and awareness in activities in the era of social media